Civil Registration and Vital Statistics for Monitoring the Sustainable Development Goals - Mills, Samuel; Abouzahr, Carla; Kim, Jane; Rassekh, Bahie M.; Sarpong, Deborah (World Bank, Washington, DC, 2017)
The United Nations Statistics Division (UNSD) defines civil registration as the continuous, permanent, compulsory and universal recording of the occurrence and characteristics of vital events pertaining to the population, as provided through decree or regulation in accordance with the legal requirements in each country. Civil registration is the best source of vital statistics since it constitutes the collection of statistics on vital events in a lifetime of a person as well as relevant characteristics of the events themselves and of the person and persons concerned. A well-functioning Civil registration and vital statistics (CRVS) system can significantly improve governance at national and subnational levels and can provide legal and protective advantages to individuals. CRVS system also has statistical advantages over censuses and sample surveys because it provides reliable disaggregated data at any geographical or administrative level, at a relatively low cost. To monitor and measure progress, the Inter-Agency and Expert Group on Sustainable Development Goal Indicators (IAEG-SDGs) was tasked with developing a global indicator framework. In addition to directly measuring the development and improvement of CRVS, data from complete and accurate CRVS systems can also provide information used to monitor other targets and indicators. CRVS systems in countries also play an important role in effecting progress in other SDG targets and indicators.